Social Attitudes in Fourth Grade Students: The Role of Augmented Reality (AR)-Assisted Bamboo Dance Cooperative Learning - I Komang Sukma Adi Winata; I Gusti Agung Ayu Wulandari; Ni Luh Putu Agetania (Jurnal Pedagogi dan Pembelajaran, 2025)
The rapid development of the modern era has influenced elementary school students’ interaction patterns, which tend to show indifference toward their surroundings. This condition may hinder the formation of essential social attitudes needed for their development in society. This study aims to critically examine the effect of the Cooperative Learning Model of the Bamboo Dance Type assisted by Augmented Reality (AR) media in enhancing students’ social attitudes. Employing a quasi-experimental design with a non-equivalent control group post-test only, the research involved 163 fourth-grade students selected through cluster random sampling from five elementary schools. Social attitude data were collected using a non-test instrument in the form of an observation rubric designed to capture students’ ability to interact, collaborate, and demonstrate tolerance during the learning process. Data were analyzed using the t-test at a 0.05 significance level. The results indicated that the t-value of 2.0416 exceeded the t-table value of 1.688, suggesting a positive and significant effect of the Cooperative Learning Model of the Bamboo Dance Type assisted by AR on students’ social attitudes. The findings highlight that integrating cooperative learning with AR technology fosters an active, collaborative, and tolerant learning environment, effectively promoting students’ understanding and internalization of social values. This study implies that such an innovative learning model provides a relevant strategy to support 21st-century educational needs.